2001
DOI: 10.1088/0957-0233/13/1/302
|View full text |Cite
|
Sign up to set email alerts
|

Convective forces in high precision mass measurements

Abstract: This paper deals with a numerical simulation of the natural convection air flow and its influence on apparent mass in high precision mass measurements. Results are in reasonable agreement with the experimental values obtained on a 1 kg silicon sphere and a 1 kg mass standard. There is clear evidence that the three-dimensional finite element model studied, allowing inclusions of the boundary and initial conditions determined experimentally, captures the most important features of convection and estimates the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…We find the determined mass differences to be in good agreement with direct numerical simulations that have been conducted together with the measurements. As being the case in high-precision mass metrology, the temperature difference between the mass and its environment is in the millikelvin range and thus by at least two orders of magnitude smaller than in the previous benchmark experiments by Gläser et al [1,2] and Mana et al [3]. Our measurements provide thus more realistic conditions close to thermal equilibrium than the studies conducted in the past.…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…We find the determined mass differences to be in good agreement with direct numerical simulations that have been conducted together with the measurements. As being the case in high-precision mass metrology, the temperature difference between the mass and its environment is in the millikelvin range and thus by at least two orders of magnitude smaller than in the previous benchmark experiments by Gläser et al [1,2] and Mana et al [3]. Our measurements provide thus more realistic conditions close to thermal equilibrium than the studies conducted in the past.…”
Section: Introductionmentioning
confidence: 49%
“…The conclusions which can be drawn agree with those of the cylindrical case. The mean slopes of the sensitivity, β , are summarized in table 1 and compared with [3] and [11]. They increase with increasing pressure in both cases reflecting the enhanced air mass density and thus the enhanced friction forces.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption effect can greatly influence mass readings of a sample cylinder by adsorption and desorption of water vapour from surrounding ambient air on the external surface of a sample cylinder (Alink et al, 2000;Mizushima, 2004Mizushima, , 2007Milton et al, 2011). The thermal effect is related to temperature gradients between a sample cylinder and the surrounding ambient air (Gläser, 1990(Gläser, , 1999Mana et al, 2002;Gläser and Borys, 2009;Schreiber et al, 2015), which is able to change the weight force of the sample cylinder through frictional forces exerted on the vertical surface of a sample cylinder and pressure forces on the horizontal surface. Both the frictional and pressure forces are caused by the upward or downward flow of air that is heated or cooled, respectively, by the sample cylinder.…”
Section: Factors For Causing Deviations Of Mass Readingsmentioning
confidence: 99%
“…The input variables used and their distributions are listed in table 6. In every trial, the air density was calculated using the equation presented in [11] and the true mass of the gas cylinder was obtained with the help of equation (4). The 0.50 0.00 0.00 0.00 0.77 0.00 0.00 0.00 c 10 u(y 10 ) 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 effect of varying shear stress was obtained with the help of equations (8)-(13) and the mass flow was calculated from equation (6).…”
Section: Numerical Methods For Calculating the Approximation For A Stamentioning
confidence: 99%
“…Constants C = −9.2 × 10 −7 g cm −2.25 K −1 and n = 1. The apparent mass change due to the natural convection of ambient air has been studied numerically with the CFDprogram by Mana et al in [4]. They found that the experimental and numerical results were in reasonable agreement.…”
Section: Introductionmentioning
confidence: 99%